Social Empowerment Strategy For Urban Poor Communities - Willya Achmad (Jurnal Ekonomi, 2024)
Urban poor communities often face complex challenges, including limited access to resources and opportunities. This research aims to analyze and identify effective social empowerment strategies for poor urban communities. This research uses a qualitative approach with descriptive methods. The research results show that overcoming poverty in urban areas requires a holistic approach that takes into account a number of interrelated and multidimensional factors. Education, employment, infrastructure, gender inequality, housing, health conditions, social mobility and environmental sustainability emerge as key elements influencing poverty levels. Integrated strategies, such as increasing access to education, establishing decent work, adequate infrastructure, overcoming gender inequality, providing affordable housing, improving health, and environmental sustainability, receive primary attention. Social empowerment through holistic strategies, including education, economic empowerment, community group formation, primary health services, and active community participation, has proven effective in increasing capacity and overcoming economic challenges.